Association of NOD1 and NOD2 genes polymorphisms with Helicobacter pylori related gastric cancer in a Chinese population - Wang, Peng (World journal of gastroenterology : WJG, 2012)
AIM：To investigate the association between the tag single nucleotide polymorphisms（TagSNPs） of NOD1 and NOD2 and the risk of developing gastric cancer.METHODS：We conducted a hospital-based case-control study including 296 incident gastric cancer patients and 160 gastritis controls.Eight TagSNPs in the NOD1 and NOD2 genes were selected from the Hapmap database using the haploview software and genotyped by the Sequenom MassArray system.The serum levels of anti-Helicobacter pylori（H.pylori） IgG were measured by enzyme-linked immunosorbent assay to indicate H.pylori infection.The odds ratios（OR） and 95% confidence intervals（CI） were calculated by unconditional logistic regression,including sex and age as confounding factors.RESULTS：The NOD1 rs2907749 GG genotype showed a decreased risk for gastric cancer（OR 0.50,95% CI：0.26-0.95,P = 0.04） while the rs7789045 TT genotype showed an increased risk（OR 2.14,95% CI：1.20-3.82,P = 0.01）.An elevated susceptibility to gastric cancer was observed in the subjects with H.pylori infection and the NaOD1 rs7789045 TT genotype（OR 2.05,95% CI：1.07-3.94,P = 0.03） or the NOD2 rs7205423 GC genotype（OR 2.52,95% CI：1.05-6.04,P = 0.04）.Haplotype analysis suggested that the distribution of AGT（rs2907749,rs2075820 and rs7789045） in NOD1 between the cases and control groups was significantly different（P corrected：0.04）,and the diplotype AGT/AGT was associated with an elevated gastric cancer risk（OR 1.98,95% CI：1.04-3.79,P = 0.04）.The association of the NOD1 rs7789045 TT genotype and the diplotype AGT/AGT was significant with H.pylori-related diffuse-type gastric cancer（OR 3.00,95% CI：1.38-6.53,P = 0.01;OR 4.02,95% CI：1.61-10.05,P 〈 0.01,respectively）.CONCLUSION：Genetic polymorphisms in NOD1 and NOD2 may interact with H.pylori infection and may play important roles in promoting the development of gastric cancer in the Chinese population.